Coronary artery disease burden relation with the presentation of acute cardiac events and ventricular fibrillation. Issue 3 (8th July 2021) - Kosmopoulos, Marinos; Bartos, Jason A.; Raveendran, Ganesh; Goslar, Tomaz; Kalra, Rajat; Hoke, Lindsay; Tsangaris, Adamantios; Sebastian, Pierre; Walser, Emily; Yannopoulos, Demetris
Abstract: Objectives: Evaluate the differences in coronary artery disease (CAD) burden between patients with ischemic resuscitated, ischemic refractory VT/VF OHCA events and N/STEMI. Background: Refractory out‐of‐hospital cardiac arrest patients presenting with initial shockable rhythms (VT/VF OHCA) have the highest mortality among patients with acute cardiac events. No predictors of VT/VF OHCA refractoriness have been identified. Methods: A retrospective cohort design was used to assess baseline characteristics, clinical outcomes, and the angiographic severity of disease among patients with VT/VF OHCA undergoing emergent coronary angiography at the University of Minnesota Medical Center. The Gensini score was calculated for all patients to assess the angiographic burden of CAD. For patients with ischemia‐related cardiac arrest, outcomes were further compared to an independent non‐OHCA population presenting with N/STEMI. Results: During the study period, 538 patients were admitted after VT/VF OHCA. Among them, 305 presented with resuscitated, and 233 with refractory VT/VF. 66% of resuscitated and 70% of refractory VT/VF had an underlying, angiographically documented, ischemic etiology. Ischemic resuscitated and refractory VT/VF had significant differences in Gensini score, (80.7 ± 3.6 and 127.6 ± 7.1, respectively, p < 0.001) and survival (77.3% and 30.0%, respectively, p < 0.001). Both groups had a higher CAD burden and worse survival than the non‐OHCA N/STEMI population (360 patients). Ischemic refractory VT/VF was significantly more likely to present with chronic total occlusion in comparison to both N/STEMI and ischemic resuscitated VT/VF. Conclusion: Ischemia‐related, refractory VT/VF OHCA has a higher burden of CAD and the presence of CTOs compared to resuscitated VT/VF OHCA and N/STEMI.